PENERAPAN MODEL PEMBELAJARAN VCT (VALUE CLARIFICATION TECHNIQUE) TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN IPS DI SEKOLAH DASAR NEGERI CIMANIS 2 SOBANG PANDEGLANG - Hakim, Zerri Rahman; Taufik, M. (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2018)
This study attempts to know what the of the application of VCT (Value Clarification Technique) learning model to the problem solving skills of V A as a class experimentation and class V B as a class control use the model learning directly to sdn attack 2 years lessons 2016/2017 on the subjects of science social especially in competence basic 2.4 appreciate the struggle of the characters in defending freedom. Methods used in research this is the method quasi ekperimen type nonequivalent control group design. Based on the results of research, show that there is a difference in problem-solving abilities between students using VCT learning models and students using direct learning models, can be seen from uji-t two parties namely 2,57 > 2,013, then H0 rejected Ha accepted. Problem-solving skills among students using a VCT learning model is higher than students who use learning model directly , can be seen from uji-t one parties that 2,57 > 1,673, so H0 rejected Ha accepted. So it will be concluded that there are differences in problem-solving abilities between students using VCT (value clarification technique) learning models with students using direct learning model.Keywords: Problem Solving, Value Clarification Technique Learning Model.